A MASTERY STUDY OF THE EXPOSITORY WRITING OF THE THIRD YEAR STUDENTS OF SMP NEGERI NAIOLA - Kefi, Irene Valentin; Sahan, Anselmus; Bouk, Edmundus (English Study Program, Faculty of Teacher Training and Educational Sciences, Universitas Timor, 2021)
This study analyzed the mastery level of students in the third year students of SMP Negeri Naiola. The aim of the study is to find out the mastery level of students about Expository Writing. The method used descriptive qualitative method. Therefore, this research used writing test. After collecting the data, the writer analyzed them based on the three generic structure of Expository Writing text namely: Thesis, Argument, and Recommendation/Reiteration. The result of data analysis shows that the students have mastered expository text. It is based on the data that their average score is 83 and categorized as Excellent. This means that the students have ability in Expository Writing. However, the students still found difficulties in in mastering argument of the components of personal expository text. The data shows that their total number of wrong answers is 48. To overcome the students’ difficulties in expository writing, English teacher have to guide and motivate the students to master expository writing based on the generic structure of the text.